Will the global financial crisis lead to lower foreign aid? A first look at United States ODA - Mendoza, Ronald U (Archīum Ateneo, 2009)
Analyzing US economic and foreign aid data from 1967 to 2007, this paper investigates whether adverse economic and financial conditions are negatively linked to official development assistance (ODA). It finds empirical evidence that US ODA has tended to decline as its economic conditions worsen. A 1 unit increase in the misery index (sum of inflation and unemployment) is associated with a roughly 0.01 percentage point decline in US ODA expressed as a share of GNI. Furthermore, an increase in financial volatility from 1 percent to 2 percent (measured by the standard deviation of the rate of return of the S&P500) is associated with a decrease in US ODA by about $2.78 billion. Informed by the empirical results in this paper, and based on very rough guesstimates, a potential decline in US ODA of anywhere from 13 to 30 percent could occur depending on the severity of the economic conditions in 2009. This predicted decline in ODA is much lower than some of the guesstimates so far by different analysts. Based on the US historical pattern, ODA is indeed at risk; nevertheless, it need not decline significantly during adverse economic times.